Proven Delivery Models for LED Public Lighting : Lease-to-Own Delivery Model in Guadalajara, Mexico - Makumbe, Pedzisayi (World Bank, Washington, DC, 2016)
Guadalajara, with a population of approximately 1.5 million, is the fourth largest city in Mexico and is located in the country’s central Pacific region. Until the implementation of the current street lighting retrofit project, the city’s outdated street lighting infrastructure had not been renovated in over 30 years. Lighting crews could not keep up with outages reported by citizens and there were many unlit areas around the city. This coincided with increasing crime rates, leading to an overall lack of safety in the city. The outdated infrastructure also required substantial spending on both maintenance and electricity for the streetlights. Street lighting represented approximately 18 percent of electricity consumption and paying for it was a significant component of the city’s budget. To help Guadalajara and other cities address the problem, Mexico’s national government established National Project for Energy Efficiency and Public Municipal Lighting (Proyecto Nacional de Eficiencia Energética en Alumbrado Público Municipal, or National Public Lighting Program). The program provides a significant amount of technical assistance to cities embarking on LED public lighting projects. This case study summarizes the implementation process of LED models for public lighting in Guadalajara.